2022
DOI: 10.1142/s2424835522720183
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of the Distal Radius by Tuberculous Osteomyelitis: A Case Report and Review of Literature

Abstract: We report a 94-year-old patient with a fractured radius that was being managed conservatively. At 2 months, an abscess was observed overlying the fracture site. An MRI scan was done and samples obtained for microbiological and pathological analyses. The patient was diagnosed with tuberculous osteomyelitis. Surgical debridement of the fracture site was performed, and the bone defect was filled with bone cement impregnated with gentamicin and rifampicin. Anti-tuberculosis therapy was administered for 9 months an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…[23] In Alejandro study on patients with tuberculous osteomyelitis and DRFs, it was found that to improve the treatment of the fracture, it is necessary to clear the inflammation (abscess) in the bone. [24] The study showed a strong correlation between platelet expression levels and DRFs, which is consistent with previous research findings. Choi [25] conducted a study on spayed female Toy Poodles with radius-ulna fractures.…”
Section: Discussionsupporting
confidence: 92%
“…[23] In Alejandro study on patients with tuberculous osteomyelitis and DRFs, it was found that to improve the treatment of the fracture, it is necessary to clear the inflammation (abscess) in the bone. [24] The study showed a strong correlation between platelet expression levels and DRFs, which is consistent with previous research findings. Choi [25] conducted a study on spayed female Toy Poodles with radius-ulna fractures.…”
Section: Discussionsupporting
confidence: 92%
“…Two of the five S. epidermidis strains were Methicillin-Resistant Staphylococcus epidermidis. The mNGS mainly identified 11 strains of anaerobes [ 31 ] and 2 strains of MTB [ 32 , 33 ]. However, the overall positive detection rate did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%